Transcranial direct current stimulation and constraint-induced therapy in cerebral palsy: A randomized, blinded, sham-controlled clinical trial. (May 2018) - Gillick, Bernadette; Rich, Tonya; Nemanich, Samuel; Chen, Chao-Ying; Menk, Jeremiah; Mueller, Bryon; Chen, Mo; Ward, Marcie; Meekins, Gregg; Feyma, Tim; Krach, Linda; Rudser, Kyle
Abstract: We investigated the safety, feasibility, and efficacy of transcranial direct current stimulation (tDCS) combined with constraint-induced movement therapy (CIMT) in children and young adults with unilateral cerebral palsy. Twenty participants were randomized to receive active or sham tDCS. The intervention consisted of 10 consecutive weekday sessions of tDCS applied to the non-lesioned hemisphere (20 min) concurrently with CIMT (120 min). Participants, caregivers, and interventionists were blinded to group assignment. The primary safety outcome investigated adverse events. The primary behavioral outcome was the Assisting Hand Assessment. All 20 participants (mean age = 12.7 yrs, range = 7.4–21.6 years) were evaluated for the primary outcomes. No serious adverse events occurred, and the most commonly reported minor adverse events were headache and itchiness. Both groups demonstrated a significant improvement in hand function after the intervention, although no significant effect of tDCS was observed (between-group difference = −2.18, 95% CI = [−6.48, 2.12], p = 0.30). Although hand function improved overall, no significant differences between intervention groups were found. Children with preserved corticospinal tract circuitry from the lesioned hemisphere, compared to those without, showed greater improvement in hand function (mean difference = 3.04, 95% CI = [−0.64, 6.72], p = 0.099). Our study demonstrates the safety and feasibility of serial sessions of tDCS, and presents preliminary evidence for the effect of CST circuitry on outcomes following tDCS/CIMT. Future work in children with unilateral cerebral palsy should focus on the optimal dosing and consider individual brain circuitry when describing response to combined interventions. Clinical Trials Registration: Clinicaltrials.gov NCT 02250092 . Highlights: tDCS and motor training in children with cerebral palsy is safe and feasible. All children improved hand function, regardless of intervention group. Children with contralateral circuitry showed greater motor improvement. Expanded research on dosing and brain circuitry in this population is indicated.